Microencapsulation of phenolic compounds from olive pomace using spray drying: A study of operative parameters. Issue 1 (June 2015) - Paini, Marco; Aliakbarian, Bahar; Casazza, Alessandro A.; Lagazzo, Alberto; Botter, Rodolfo; Perego, Patrizia
Abstract: In this work, polyphenols from olive pomace were extracted with a high pressure-high temperature agitated reactor and for the first time encapsulated by spray drying, using maltodextrin as coating agent at different concentrations. In addition, effects of inlet temperature (130 °C and 160 °C) and feed flow (5 mL/min and 10 mL/min) were studied. Physicochemical, antioxidant properties and stability of microparticles were evaluated. High inlet temperature implied lower moisture and bulk density without affecting antioxidant properties. Increasing maltodextrin concentration caused lower bulk density and higher microparticles sizes, while higher feed flow lead to increased moisture content. Spray drying at inlet temperature of 130 °C, maltodextrin concentration of 100 g/L and feed flow of 10 mL/min, resulted in high microencapsulation yield (94%) and encapsulation efficiency (76%) with high polyphenols content (39.5 mgCAE /gDP ) and antiradical power (33.8 mmolDPPH /Lextract ). HPLC and thermogravimetric analysis revealed the thermal protection effect of maltodextrin for phenolic compounds. Microcapsules were stable at 5 °C in dark condition for 70 days, and only 21% were degraded increasing storage temperature up to 25 °C. UV light exposure resulted in a 66% loss in polyphenols after 48 h of exposure. Highlights: Phenolic extract of olive pomace was spray dried at different operative parameters. Average particle size was smaller than 100 μm. Maximum polyphenol encapsulation yield was 39.5 mgCAE /gDP . Microparticles had antiradical power from 3.6 to 33.8 mmolDPPH /Lextract . Only 21% of microencapsulated phenolics were degraded at 25 °C after 70 days.